Perancangan Miniatur Smart Greenhouse untuk Sistem Penyiraman dan Monitoring Tanaman Secara Otomatis - Jesetua Natanael Simorangkir; Eka Dodi Suryanto; Dian Putra Saragi (JOURNAL SAINS STUDENT RESEARCH, 2026)
The advancement of technology in the agricultural sector has spurred the implementation of automation systems to optimize efficiency and productivity through the Internet of Things (IoT) concept. This study aims to design and implement an integrated ESP32 microcontroller-based Smart Greenhouse system for real-time monitoring and control of environmental parameters. The system architecture integrates a series of sensors including soil moisture, temperature, light intensity, and motion sensors, supported by an LCD as a local interface and the Blynk application for remote monitoring. The methodology used is an experimental system engineering design approach that includes the design, implementation, and performance testing phases. The test results show that the system is capable of accurately acquiring environmental data and disseminating information synchronously through local and cloud platforms. In addition, the automatic control mechanism is proven effective in activating water pump actuators based on fluctuations in soil moisture parameters with a short response time. These findings confirm that the implementation of an IoT-based Smart Greenhouse system can improve the efficiency of crop management through watering automation and remote monitoring. This research has the potential to be developed on an industrial scale with optimization of sensor precision and network connectivity stability.